2022
DOI: 10.1017/s0958344022000039
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an AI chatbot as an English conversation partner in EFL speaking classes

Abstract: With the growth of chatbots, concerns about implementing artificial intelligence (AI) chatbots in educational settings have consistently arisen, especially for the purpose of language learning. This study introduced a task-based voice chatbot called “Ellie”, newly developed by the researchers, and examined the appropriateness of its task design and performance as an English conversation partner and students’ perceptions on using it in EFL class. Korean EFL learners (N = 314) aged 10–15 years performed three sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…For example, virtual reality and augmented reality tools can improve language learning by immersing students into virtual worlds [14]. AI chatbots served as conversation partners in language-speaking classes [15]. Among the emerging technologies, machine translation (MT) also transformed existing teaching methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, virtual reality and augmented reality tools can improve language learning by immersing students into virtual worlds [14]. AI chatbots served as conversation partners in language-speaking classes [15]. Among the emerging technologies, machine translation (MT) also transformed existing teaching methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Descriptive studies, theoretical studies, conference proceedings, case studies, qualitative studies, observational studies Other than open-access studies Other (less reputable) databases Other languages The studies of the research scope, i.e., those which did not investigate the use of chatbots in EFL at a university level, e.g., Yang et al (2022) …”
Section: Methodsmentioning
confidence: 99%
“…The studies of the research scope, i.e., those which did not investigate the use of chatbots in EFL at a university level, e.g., Yang et al (2022) …”
Section: Methodsmentioning
confidence: 99%
“…Most of the studies reported the use of chatbots for language learning by students in higher education (e.g., undergraduate and postgraduate students). However, there are also studies focusing on primary and secondary school students, such as [ 29 , 32 ], which shows a positive impact on students acquiring English as a foreign language.…”
Section: Literature Reviewmentioning
confidence: 99%